Systematic Literature Review: Model Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Kritis Matematika - Barus, Janna Sri Bina Br; Meiliasari, Meiliasari (Universitas Muria Kudus, 2025)
This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model, the tools or media that can support the PBL model, and the challenges faced when implementing the PBL model to enhance students' mathematical critical thinking skills. The method used is a Systematic Literature Review (SLR), reviewing thirteen primary research articles focused on junior high and senior high schools. After reading, identifying, and analyzing these thirteen articles, it was found that PBL can generally improve students' mathematical critical thinking skills. However, no effect was observed on students with low Self-Regulated Learning (SRL) or those with a Concrete Sequential (CS) thinking style. Several tools that can support PBL in improving students' mathematical critical thinking skills include Student Worksheets (LKS), Question Cards, the Ispring application, and the Classwiz Emulator. Two issues were identified in implementing the PBL model to improve students' mathematical critical thinking skills: first, students' interest in solving problems, and second, the significant amount of time required to apply the PBL model effectively.